Creatio ex Nihilo and Romans 4.17 in Context - Worthington, Jonathan D. (New Testament studies, 2016)
Rom 4.17d is often read as referring to creation, perhaps even creatio ex nihilo. Others argue that this doctrine was not yet conceptually available. After exploring what nothing' means in similar phrases in Paul's ancient context (2 Macc 7.28 and Philo), the first conclusion is that if Rom 4.17d refers to creation then Paul's nothings' most likely do not refer to an absolute nihil. However, after exploring Rom 4.17 in the context of Paul's argument, the final conclusion is that in Rom 4.17d Paul does present absolute nothings', though in God's speech to Abraham, not at creation. Paul's theology encompasses God's authority and causation ex nihilo.